Analysis of sun protection factor (SPF) values of facial cream cosmetics marketed in Sidenreng Rappang Regency - Lidiawati, Dewi; Mubarak, Syahrul; Ashari, Asriyana; Pare Rombe, Yunita (Arfak Chem: Chemistry Education Journal, 2025)
Sun Protection Factor (SPF) is a critical indicator of a sunscreen’s ability to protect the skin from ultraviolet B (UVB) radiation. Accurate SPF determination is essential to ensure product efficacy, regulatory compliance, and consumer safety. This study aimed to quantitatively evaluate the SPF values of commercial facial sunscreen creams circulating in Sidenreng Rappang Regency and to compare the measured values with the corresponding label claims. An analytical in vitro SPF assessment was conducted using UV–Vis spectrophotometry based on the Mansur method. Three products with SPF 30, SPF 40, and SPF 50 label claims were analyzed. The results revealed that all measured SPF values were substantially lower than the stated claims. Sample A (SPF 30), Sample B (SPF 40), and Sample C (SPF 50) exhibited SPF values of 19.29, 21.37, and 21.63, respectively. These findings demonstrate inconsistencies between labeled and experimentally determined SPF values, underscoring the need for rigorous quality control, routine verification of SPF claims, and improved oversight of sunscreen products in the market.